Emerging targets in treating pain. Issue 4 (August 2015) - Chang, David S.; Raghavan, Rahul; Christiansen, Sandy; Cohen, Steven P.
Abstract : Purpose of review: To provide an overview on drug targets and emerging pharmacological treatment options for chronic pain. Recent findings: Chronic pain poses an enormous socioeconomic burden for the more than 30% of people who suffer from it, costing over 600 billion per year in the USA. In recent years, there has been a surge in preclinical and clinical research endeavors to try to stem this epidemic. Preclinical studies have identified a wide array of potential targets, with some of the most promising translational research being performed on novel opioid receptors, cannabinoid receptors, selective ion channel blockers, cytokine inhibitors, nerve growth factor inhibitors, N -methyl-D-aspartate receptor antagonists, glial cell inhibitors, and bisphosphonates. Summary: There are many obstacles for the development of effective medications to treat chronic pain, including the inherent challenges in identifying pathophysiological mechanisms, the overlap and multiplicity of pain pathways, and off-target adverse effects stemming from the ubiquity of drug target receptor sites and the lack of highly selective receptor ligands. Despite these barriers, the number and diversity of potential therapies have continued to grow, to include disease-modifying and individualized drug treatments.